Temperature changes in a low-profile,cross-ventilated building in the high plains - Joseph P. Harner; John F. Smith (Kansas Agricultural Experiment Station Research Reports, 2009)
Performance of an evaporative cooling system was evaluated in the High Plains in a low-profile, cross-ventilated dairy facility housing 4,200 lactating cows. The temperature decrease across the 6-inch cellulose evaporative pad during the afternoon hours from July 15 to August 14, 2008, was 12.6°F. The temperature-humidity index was below 72 for 14 and 19 hours/day in pens near the outlet (exhaust fans) and inlet (near evaporative cooling pad), respectively, compared with 12 hours under ambient conditions. Throughout the study period, the evaporative cooling system decreased the number of hours that cows were housed in a heat stress environment irrespective of pen location in the building.; Dairy Day, 2009, Kansas State University, Manhattan, KS, 2009; Dairy Research, 2009 is known as Dairy Day, 2009
Keywords: Kansas Agricultural Experiment Station contribution; no. 10-103-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1021; Dairy Day; 2009; Dairy; Dairy facilities; Heat stress; Temperature; Ventilation